EMBEDDED LINUX BASED ALBUM BROWSER SYSTEM AT MUSIC STORES - Suryadiputra Liawatimena (JUTI: Jurnal Ilmiah Teknologi Informasi, 2009)
The goal of this research is the creation of an album browser system at a music store based on embedded Linux. It is expected with this system; it will help the promotion of said music store and make the customers activity at the store simpler and easier. This system uses NFS for networking, database system, ripping software, and GUI development. The research method used are and laboratory experiments to test the system’s hardware using TPC-57 (Touch Panel Computer 5.7" SA2410 ARM-9 Medallion CPU Module) and software using QtopiaCore. The result of the research are; 1. The database query process is working properly; 2. The audio data buffering process is working properly. With those experiment results, it can be concluded that the summary of this research is that the system is ready to be implemented and used in the music stores.